Ionising radiation exposure-induced regulation of selected biomarkers and their impact in cancer and treatment - Mzizi, Yonwaba; Mbambara, Saidon; Moetlhoa, Boitumelo; Mahapane, Johncy; Mdanda, Sipho; Sathekge, Mike; Kgatle, Mankgopo (Frontiers in Nuclear Medicine, 2024)
Ionising radiation (IR) is a form of energy that travels as electromagnetic waves or particles. While it is vital in medical and occupational health settings, IR can also damage DNA, leading to mutations, chromosomal aberrations, and transcriptional changes that disrupt the functions of certain cell regulators, genes, and transcription factors. These disruptions can alter functions critical for cancer development, progression, and treatment response. Additionally, IR can affect various cellular proteins and their regulators within different cell signalling pathways, resulting in physiological changes that may promote cancer development, progression, and resistance to treatment. Understanding these impacts is crucial for developing strategies to mitigate the harmful effects of IR exposure and improve cancer treatment outcomes. This review focuses on specific genes and protein biomarkers regulated in response to chronic IR exposure, and how their regulation impacts disease onset, progression, and treatment response.